2019
DOI: 10.3390/ijms20020415
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Changes in Tomato Cell Walls in Roots and Fruits: The Contribution of Arbuscular Mycorrhizal Colonization

Abstract: Modifications in cell wall composition, which can be accompanied by changes in its structure, were already reported during plant interactions with other organisms, such as the mycorrhizal fungi. Arbuscular mycorrhizal (AM) fungi are among the most widespread soil organisms that colonize the roots of land plants, where they facilitate mineral nutrient uptake from the soil in exchange for plant-assimilated carbon. In AM symbiosis, the host plasma membrane invaginates and proliferates around all the developing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
1
10
0
2
Order By: Relevance
“…Indeed, the fungi hyphae can capillary explore wider soil volume than the root hair, thus allowing the plants to uptake water even under severe deficit conditions; in addition, the more the root colonization augments the more the stomatal conductance to water vapor increases up to 10 fold compared to lightly colonized plants [28]. Moreover, changes in cell wall composition of both roots and fruits may also be elicited by the inoculation of tomato plants with Funneliformis mosseae [29].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the fungi hyphae can capillary explore wider soil volume than the root hair, thus allowing the plants to uptake water even under severe deficit conditions; in addition, the more the root colonization augments the more the stomatal conductance to water vapor increases up to 10 fold compared to lightly colonized plants [28]. Moreover, changes in cell wall composition of both roots and fruits may also be elicited by the inoculation of tomato plants with Funneliformis mosseae [29].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding these results, the tomato plants had a better response to the application of arbuscular mycorrhizal fungi related to the use of chitosan and humic acid, independently of the cultivar used, which could have been related to the versatility of these microorganisms (Martanto et al, 2018;Piculell et al, 2018;Chialva et al, 2019)which can be accompanied by changes in its structure, were already reported during plant interactions with other organisms, such as the mycorrhizal fungi. Arbuscular mycorrhizal (AM.…”
Section: Cultivares / Cultivarsmentioning
confidence: 82%
“…No obstante, a estos resultados, las plantas de tomate tuvieron una mejor respuesta a la aplicación de hongos micorrízicos con relación al uso del quitosano y el ácido húmico con independencia del cultivar utilizado, efecto que pudiera estar relacionado a la versatilidad de estos microorganismos (Martanto et al, 2018;Piculell et al, 2018;Chialva et al, 2019). Algunos de los efectos más notorios está relacionado con su influencia en la nutrición mineral sobre todo de P y N así como la absorción de agua por las raíces, su función protectora contra microorganismos patógenos, pero además conf ieren a las plantas tolerancia a diferentes in the plant.…”
Section: Cultivares / Cultivarsunclassified
“…Numerous studies have sought to analyze cell wall dynamics in response to environmental stress, such as changes in the quality and quantity of light, submergence, dehydration, desiccation, and freezing [ 102 , 103 , 104 , 105 , 106 ]. In addition to abiotic stresses, changes in wall architecture have been widely reported in response to biotic stresses, including pathogen infection and parasitism [ 107 , 108 , 109 , 110 , 111 ]. Furthermore, the significance of cell wall dynamics has been highlighted in plant–plant interactions with parasitic plants, as well as with microbes, fungi, and insect pests [ 112 , 113 ].…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%